Program olahraga : menopause / Barbara Bushman, Janice Clark Young; pengalih bahasa, Rachma, Ervina; penyunting, Andina Ken Soraya, Rizka - BUSHMAN, Barbara; YOUNG, Janice Clark; RACHMA; ERVINA; ANDINA KEN SORAYA; RIZKA (Citra Aji Parama, 2012)
vii, 223 hlm. : ilus. ; 30 cm.